THE APPLICATION OF ACTIVE CYCLE OF BREATHING TECHNIQUE (ACBT) TO IMPROVE AIRWAY CLEARANCE IN CHILDREN WITH BRONCHOPNEUMONIA - Handayani, Dwining; Sari, Mia Yuspita (Faculty of Nursing and Midwifery, Binawan University, 2025)
Bronchopneumonia is a respiratory tract infection that often affects children, with the main problem being ineffective airway clearance. This disease is caused by microbes or foreign substances entering the bronchioles and alveoli, leading to inflammation and the production of excessive sputum, which accumulates and obstructs the airways. If ineffective airway clearance is not managed promptly, it can cause shortness of breath and may even lead to death due to insufficient oxygen supply. The Active Cycle of Breathing Technique (ACBT) can be an alternative intervention to address ineffective airway clearance in patients with bronchopneumonia. The aim of this study is to describe the application of ACBT in bronchopneumonia patients experiencing ineffective airway clearance. This study used a case study design with a nursing process approach. Data were collected through interviews, observation, physical examination, and documentation. The results of nursing implementation over three days showed that applying ACBT for 10–15 minutes reduced shortness of breath, achieved a respiratory rate of 22 breaths per minute, and eliminated dyspnea, thus resolving the problem. It can be concluded that ACBT is effective in overcoming ineffective airway clearance in patients with bronchopneumonia. Implementing ACBT in healthcare services with proper approaches, education, and adaptation to the child’s age and ability can help clear the airway without complications.